Faktor yang Mempengaruhi Kinerja Guru MI Kecamatan Paiton Kabupaten Probolinggo Jawa Timur - Moch Misbahul Anwar (At- Ta'lim : Jurnal Pendidikan, 2015)
This research has an objective to know: (1) the performance of Madrasah Ibtidaiyah teacher in sub district Paiton (2) the influence of teaching skill perception about work environment, and work motivation to performance of MI Insan Terpadu Paiton. Next, this research uses after the fact research that uses proportional random sampling from population which is collected from 99 teachers of Madrasah Ibtidaiyah and it is acquired 55 teachers sample. Data collection technique to know teacher performance and their skill is collected from the observation. Then, the perception of work environment and work motivation is taken from questionnaire scale Likert with 4 scale modification. The, Data analysis technique which is used is descriptive, partial correlation and double regression to degree 5% significant. The result of descriptive analysis shows that the level of teacher performance is in good category (average = 100,93 from minimum score 119). The result of partial correlation shows that there is significant influence from variables of teaching skill, perception of work environment and work motivation to teacher performance in a row. r1y (2,3) about 0,647; r2y (1,3) about 0,367; r3y (1,2) about 0,271. The result of double regression show correlation coefficient R about 0,774. The significant influence of Ry (1,2,3) can be seen in from the significant of determination of coefficient (R2) about 59,29%. The significant of effective contribution is acquired from the teaching skill 52%; perception of work environment about 4,8%; working motivation 3,2%.